2011
DOI: 10.2165/11538590-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine as a Potential Ergogenic Aid in Healthy Subjects

Abstract: Dietary supplements containing L-arginine, a semi-essential amino acid, are one of the latest ergogenic aids intended to enhance strength, power and muscle recovery associated with both aerobic and resistance exercise. L-arginine is claimed to promote vasodilation by increasing nitric oxide (NO) production in the active muscle during exercise, improving strength, power and muscular recovery through increased substrate utilization and metabolite removal, such as lactate and ammonia. Research on L-arginine has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 107 publications
1
83
0
3
Order By: Relevance
“…We have found that food supplement ARGI+ has more appreciable influence on increasing single muscle capacity power and anaerobic alactic muscle power than using 20 days ARGI+ in combination with Multi Maca. As reported by T. Álvares et al (2011) [19] dietary supplements, containing L-arginine, helps to increase muscle strength, their recovery after anaerobic and aerobic exercise, removing metabolic products. Reasonable results were obtained by V. Imanipour et al (2012) [13], who studied the effects of L-arginine on methabolism and anaerobic capacity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have found that food supplement ARGI+ has more appreciable influence on increasing single muscle capacity power and anaerobic alactic muscle power than using 20 days ARGI+ in combination with Multi Maca. As reported by T. Álvares et al (2011) [19] dietary supplements, containing L-arginine, helps to increase muscle strength, their recovery after anaerobic and aerobic exercise, removing metabolic products. Reasonable results were obtained by V. Imanipour et al (2012) [13], who studied the effects of L-arginine on methabolism and anaerobic capacity.…”
Section: Discussionmentioning
confidence: 84%
“…T. Alvares et al (2011) [19] concludes, that the intake of L-arginine improves the blood flow, so the muscles are better supplied with the necessary substances. Moreover it also promotes greater removal of metabolities, such as lactate and ammonia Study data showed, that L-arginine intake improves metabolic process, stimulates muscles cells and inhibits fat cells proliferation, which increases muscle mass, improves muscular recovery and decreases fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements containing arginine, a semiessential amino acid, are one of the latest ergogenic aids intended to enhance strength, power and muscle recovery associated with both aerobic and resistance exercise [1]. It appears that there is an increasing interest in arginine-based supplements, and, therefore, more knowledge about its effects in healthy physically active subjects is needed [1].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that there is an increasing interest in arginine-based supplements, and, therefore, more knowledge about its effects in healthy physically active subjects is needed [1]. Arginine administration has been claimed to promote an increase in blood perfusion in the active muscle [2], increasing substrates necessary for improving muscular recovery and protein synthesis during and/or after exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation